The role of unions in addressing behavioural market failures. (November 2021) - Harcourt, Mark; Gall, Gregor; Kumar, Rinu Vimal; Croucher, Richard
The traditional view of economists is that unions cause market failures, thereby reducing economic efficiency. Freeman and Medoff challenged this overly negative view, suggesting unions address market failures associated with the 'public goods' aspects of terms and conditions in the workplace for members and non-members alike. This article builds upon their work by arguing workers' collective voice via unions can also be used to address particular behavioural market failures associated with common defects in individual cognition. Specifically, the article suggests how unions through membership, expert and organisational learning effects can help address four common behavioural market failures or cognitive mistakes, namely, short-termism, inattention to important but hidden attributes, unrealistic optimism, and poor probability estimation. In order to explore how the three effects help mitigate the four failures, the article draws upon insights from behavioural economics. Finally, it discusses the factors which influence the extent of the application of the three effects.